The perception of small and medium enterprises (smes) on the implementation of sales and services (sst) tax - Baldev Raj, Kasmira Gupta (2019)
Malaysian government had replaced Goods and Service Tax (GST) with Sales and Services Tax (SST) on 1st September 2018. This study was conducted to explore the perception of Small and Medium Enterprise (SME) on the implementation of SST 2.0 in Malaysia based on the level of acceptance, awareness, attitude, understanding, preparedness and probable area of difficulties towards the SST 2.0 implementation in Malaysia. The Malaysian SMEs are concerned with the SST implementation impact on their organization. Six variables are used to explore the perception of SMEs towards the implementation of SST. The variables used are level of acceptance, awareness, attitude, understanding, preparedness and probable area of difficulties. In total 116 respondents out of the 250 among the SMEs participated in this research who are randomly selected. The data were collected and analyzed using the technique of descriptive statistics on the demographic and mean score on six constructs to know the level of each variable towards the SST implementation among SMEs in Malaysia. The study shows that all variables have a mean more than 3.70 and this show the SMEs in Malaysia agrees on the issues of SST implementation. Recommendations to the taxpayers are application of technologies to overcome area of difficulties, to educate the taxpayers to promote preparedness, educating the young for favorable attitude and influencing compliance through promoting awareness. The future studies could include on other states of Malaysia followed by to replicate the other aspect of indirect tax and the same questionnaire can be used to explore different perspectives of tax.